Polymicrobial synergy and dysbiosis in inflammatory disease - Lamont, Richard J. (Trends Mol Med, 2014)
Uncontrolled inflammation of the periodontal area may arise when complex microbial communities transition from a commensal to a pathogenic entity. Communication among constituent species leads to polymicrobial synergy among metabolically compatible organisms that acquire functional specialization within the developing community. Keystone pathogens, even at low abundance, elevate community virulence and the resulting dysbiotic community targets specific aspects of host immunity to further disable immune surveillance while promoting an overall inflammatory response. Inflammophilic organisms benefit from proteinaceous substrates derived from inflammatory tissue breakdown. Inflammation and dysbiosis reinforce each other and the escalating environmental changes further select for a pathobiotic community. We have synthesized the polymicrobial synergy and dysbiotic components of the process into a new model for inflammatory diseases.